Role of GeneXpert MTB/Rif Assay in Diagnosing Tuberculosis in Pregnancy and Puerperium - Zaiyad G. Habib; Farouq M. Dayyab; Abdallah Sanda; Sirajo H. Tambuwal; Mahmood M. Dalhat; Hamza Muhammad; Garba Iliyasu; Ibrahim Nashabaru; Abdulrazaq G. Habib (Case Reports in Infectious Diseases)
Presentation of tuberculosis (TB) in pregnancy may be atypical with diagnostic challenges. Two patients with complicated pregnancy outcomes, foetal loss and live premature delivery at 5 and 7 months of gestation, respectively, and maternal loss, were diagnosed with pulmonary TB. Chest radiography and computed tomography showed widespread reticuloalveolar infiltrates and consolidation with cavitations, respectively. Both patients were Human Immunodeficiency Virus (HIV) seronegative and sputum smear negative for TB. Sputum GeneXpert MTB/Rif (Xpert MTB/RIF) was positive for Mycobacterium tuberculosis. To strengthen maternal and childhood TB control, screening with same-day point-of-care Xpert MTB/RIF is advocated among both HIV positive pregnant women and symptomatic HIV negative pregnant women during antenatal care in pregnancy and at puerperium.